Assessments of Noise Levels From Noise Sources in Akure, Nigeria: A Preliminary Study - Abulude, Francis Olawale; Fagbayide, Samuel Dare; Akinnusotu, Akinyinka (Iraqi Journal of Science, 2018)
Background: Noise injury and hearing loss are significant problems in Nigerian community. The hearing loss sustained from noise injury can have disabled personnel and social consequences for the affected persons and their families. This study was carried out to quantify the noise level of over eighty (80) different sources using the sound level meter (GB: 2266204) at different locations in Akure, capital of Ondo State, Nigeria. Standard procedure specified by the manufacturer was strictly followed and the results were statistically analyzed. The range of results obtained were: household products (48.5±0.5 - 105.7±3.2dBA), traffic (60.9±0.6 - 77.5±1.2dBA), market (55.0±0.5 - 68.1±0.7dBA), automobile/ workshop (65.7±0.5 - 105.7±3.3dBA), poultry/livestock (48.7±0.5 - 60.7±0.7dBA), musical instrument (45.0±0.5 - 79.3±1.3dBA), residential areas (41.2±0.5 - 46.3±0.5), farm machinery/tools (76.4±1.2 - 99.3±1.5dBA), hospital (48.0±0.5 - 61.1±0.6dBA), and baby toys (42.7±0.5 - 50.9±0.5dBA). The results showed that many of the sources exceeded the standard limits proposed by WHO, FEPA, OSHA and that of countries like Germany, Australia, Japan, Korea, and the Philippines.Conclusion: The results show the existence of noise pollution in Akure, thus the need for noise control in this area. It is recommended that the Nigerian government should put an effort to reduce noise pollution in the country. This can be achieved by creating awareness of the danger of noise pollution and putting up necessary sanctions.